Les cabinets scientifiques dans les lycées au XIXe siècle et leur conservation - Henri Chamoux (In Situ)
Because they were aimed at preparing pupils for the grandes écoles (the elite higher education institutions), the French lycées were equipped in the 19th century with rich collections of scientific instruments. Some schools even inherited collections dating back to the 18th century. A little more than a hundred schools today house a great number of instruments, which were built by a hundred Parisian manufacturers, mostly active around the Latin Quarter. But with rare exceptions, these collections are ill preserved. The descriptive inventories of these items cannot guarantee their adequate protection, meaning their fate depends for the most part on the school staff itself. Educational activities and publications around these instruments make it at least possible to let the greatest number of people discover their existence.